(3GdfXQjGJ , GdYedjGJ , GdhSGFW , GdcaGjGJs - (3gGOj(B, (3fgQs; (3GdNWjH CMeO(B, s ((3GQHO(B:s (3YGde GdcJH GdMOjK(B,s, 2009)
(3GddZI h GdcdGe aj Gdeaghe GddSGfj GdMOjK , Hjf GdQeR h GdGTGQI h GdYdGeI , GddSGfjGJ h GdGYdGe , GdGJUGd GdGfSGfj (B: (3Gdeaghe h GdfXQjI h GdCgOGa , NUGFU YedjI GdGJUGd hhSGFd GdGJUGd h GdGYdGe , GdcaGjGJ GdGJUGdjI h GdGYdGejI , GOGQI GdebGHdGJ , GdGJUGd GdGOGQj GOGQI GdeYQaI h fXe GOGQI GdeYdheGJs
Keywords: (3GdGJUGds; (3GdGJUGd `` EOGQIs